IT PROJECT MANAGER’S COMPETENCIES – SYSTEMATIC LITERATURE REVIEW - Zemlińska-Sikora, Urszula (Organizacja i Kierowanie, 2023)
In modern organizations, numerous processes have evolved as a result of digital transformation. Today’s business operations increasingly incorporate project-based approaches. The COVID-19 pandemic accelerated changes that brought on by the transformation of the IT sector. The field of IT project management is both fascinating and rapidly evolving. Appropriate collaboration between project team members, facilitated by a designated Project Manager (PM), is essential for the IT project’s success. However, the specific competencies that an IT PM should possess are not clearly defined. This study aims to present research grounded in competency models and project management methodologies, alongside a systematic literature review of IT PM competencies. From the conducted work, a list of competencies has been compiled, identifying sustainability, digital intelligence, and emotional intelligence as potential emerging competencies. Additionally, limitations and future research directions AChave been discussed.